Soy molasses as a feed ingredient for finishing cattle - Schoenholz, C.K.; Hunter, R.D.; Nutsch, T.A.; Drouillard, James S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Eighty Angus × Hereford cross steers were used in an individual feeding study to compare soybean molasses (a by-product of soybean meal manufacture) and soybean meal as ingredients in finishing diets containing flaked corn or a combination of high-moisture corn and dryrolled corn. Supplementation with soy molasses resulted in higher (P<.05) feed intakes in the cattle fed the high-moisture corn diet but had no effect on intakes of cattle fed the flaked diets. No such changes were noted for supplementation with soybean meal. In general, carcass traits were not influenced by level or type of supplement. Soy molasses appears to have feed value equal to or greater than that of soybean meal when compared on a protein basis. Its value as a source of supplemental nutrients appears to be greater in steam-flaked diets than in high-moisture diets.
Keywords: Beef; Soy molasses; Degradable intake protein; Finishing cattle